Modelling the Effect of Human Heterogeneity on Infectious Disease Transmission Dynamics (CSIAM Transactions on Life Sciences, 2025)
Human heterogeneity is a critical issue in infectious disease transmissiondynamics modelling, and it has recently received much attention in COVID-19 studies. In this article, a general human heterogeneous disease model with mutation isproposed to comprehensively study the effects of human heterogeneity on basic reproduction number, final epidemic size and herd immunity. We show that humanheterogeneity may increase or decrease herd immunity level, strongly depending onsome convexity of the heterogeneity function, which gives new insights and extendsthe results in [Britton et al., Science, 369: 846–849, 2020]. Moreover, human heterogeneity may decrease the basic reproduction number but increase the level of herd immunity, implying the unreliability of the basic reproduction number in characterizing thespread and control of infectious diseases with human heterogeneity.